Clinical Re-Audit of Baseline Assessment, Consideration of Medication, Titration, and Monitoring of Service Users With a Working Diagnosis of ADHD (Attention Deficit Hyperactivity Disorder) in South Durham Tier 3 CAMHS. - Mabel Oduma; Thamara Athauda (BJPsych Open)
Aims: This is a re- audit to assess if the same national guidelines in terms of commencement of medications, response to treatment, follow-up, pre/post treatment physical health monitoring, and use of rating scales are being followed for service users with working, but as yet confirmed, diagnoses of ADHD and ascertain utilization of recommendations from previous audit completed in December 2022.